Pemanfaatan Chatbot AI dalam Menjawab Pertanyaan Keislaman di Kalangan Mahasiswa Pendidikan Islam (Pusat Riset dan Inovasi Nasional, 2026)
The development of Artificial Intelligence (AI) in the 21st century has brought significant transformation to the field of education, including Islamic Religious Education (PAI). One of the most practical implementations of this technology is the chatbot an automated conversational system capable of providing quick and contextual responses to user queries. This study aims to analyze the utilization of AI-based chatbots in addressing Islamic-related questions among students of the Islamic Education Department at IAIN Kerinci. The research employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The findings reveal that students use chatbots as an initial source of information to understand Islamic concepts such as fiqh, tafsir, and hadith. Chatbots serve as learning aids that promote active learning and enhance students’ digital religious literacy. However, the study also identifies limitations related to the accuracy and validity of the sources used by the system, indicating that students still need verification from lecturers and authoritative Islamic literature. Overall, AI-based chatbots hold great potential to support interactive and contextual Islamic learning, provided their use is guided by academic supervision rooted in Islamic values.